Two Gut Microbiota-Derived Toxins Are Closely Associated with Cardiovascular Diseases: A Review - Tomoya Yamashita; Naofumi Yoshida; Takuo Emoto; Yoshihiro Saito; Ken-ichi Hirata (Toxins, 2021)
Cardiovascular diseases (CVDs) have become a major health problem because of the associated high morbidity and mortality rates observed in affected patients. Gut microbiota has recently been implicated as a novel endocrine organ that plays critical roles in the regulation of cardiometabolic and renal functions of the host via the production of bioactive metabolites. This review investigated the evidence from several clinical and experimental studies that indicated an association between the gut microbiota-derived toxins and CVDs. We mainly focused on the pro-inflammatory gut microbiota-derived toxins, namely lipopolysaccharides, derived from Gram-negative bacteria, and trimethylamine N-oxide and described the present status of research in association with these toxins, including our previous research findings. Several clinical studies aimed at exploring the effectiveness of reducing the levels of these toxins to inhibit cardiovascular events are currently under investigation or in the planning stages. We believe that some of the methods discussed in this review to eliminate or reduce the levels of such toxins in the body could be clinically applied to prevent CVDs in the near future.